Livestock depredations and attitudes of local pastoralists toward carnivores in the Qinghai Lake Region, China. Issue 4 (1st July 2015) - Li, Chunlin; Jiang, Zhigang; Li, Chunwang; Tang, Songhua; Li, Feng; Luo, Zhenhua; Ping, Xiaoge; Liu, Zhao; Chen, Jing; Fang, Hongxia
Abstract : As human population increase, human‐wildlife conflicts have reached unprecedented levels, often resulting in negative attitudes toward regional conservation initiatives, and thus are of concern for conservation communities. From April to May 2011, we carried out a survey to quantify carnivore‐induced livestock losses perceived by local pastoralists in the Qinghai Lake region on the pastoral Qinghai—Tibetan Plateau and examined the ecological and socio‐economic dimensions in the conflict. We finished 286 in‐person interviews using a semi‐structured questionnaire with mixed closed‐ and open‐ended questions. Our results showed that 93.7% of the respondents reported livestock depredations by carnivores from March 2010 to March 2011. The perceived losses represented 3.7% of total standing value of livestock in the region. The losses were positively correlated with livestock number in each household and showed significant seasonal and diurnal difference. Adult sheep and goats were the mostly killed (54.9%), followed by lambs (21.0%), adult yaks and cattle (19.1%), calves (4.9%) and horses (0.1%). More than 80% of the respondents reported that they could not tolerate the contemporaneous depredations and nearly two thirds expected compensations for their losses. Wolf Canis lupus was blamed for most of the killings (76.0%) and was perceived most negative followed by brown bear Ursus arctos, Tibetan fox Vulpes ferrilata, red fox Vulpes vulpes and raptors. Attitudes toward the problem carnivores were positively correlated with livestock size but negatively with magnitudes of the depredations. The attitudes also varied among the three survey sites, which may be attributed to the different extent of openness and livelihood dependence on animal husbandry. In the light of our results, we suggested possible measures to mitigate the conflict and maintain coexistence between human and wild carnivores on the Qinghai—Tibetan Plateau.